(untitled) (Literasi Nusantara, 2025)
Character education is one of the essential aspects of higher education. A strong and noble character helps students become individuals of integrity, responsibility, and positive contributions to society. This study aims to examine how character education instills academic ethics in the era of globalization. The research method used is qualitative, with data collection techniques through interviews and observations. The results show that character education effectively fosters strong academic ethics and noble values. This study also emphasizes the importance of students’ roles in developing strong and noble character through academic and non-academic activities. The conclusion affirms that character education plays a vital role in shaping strong academic ethics in the era of globalization. Through academic and non-academic activities, students can develop integrity, responsibility, and positive contributions to society. Therefore, character education should continue to be reinforced in higher education.